Reconstructing the Distribution of Inheritance in Islamic Family Law: Normative and Contextual Analysis in Indonesia - Muklisin, Muklisin (Rechtsvinding, 2025)
Inheritance disputes remain a common source of conflict in Muslim families in Indonesia, reflecting tensions between classical fiqh provisions, the Compilation of Islamic Law (KHI), customary practices, and judicial interpretation. This article reassesses the principles of inheritance distribution in Islamic Family Law and develops a reconstruction that is faithful to scripture while responsive to contemporary justice. Using a library research design with a normative-juridical approach, the study applies content analysis to primary sources (the Qur’an, Hadith, fiqh manuals of the four schools, and the KHI) and secondary sources (recent books, journal articles, and selected judicial rulings). The findings highlight three points: (1) legitimate juristic discretion—such as obligatory bequest, hibah, and amicable settlement—can bridge the gap between strict faraidh ratios and contextual justice; (2) Indonesian judicial practice tends to accommodate family welfare but lacks a consistent assessment framework; and (3) disputes often recur in determining heirs, classifying joint property, and applying the 2:1 ratio where female heirs face social or economic vulnerability. This study proposes a threefold test—justice (al-‘adalah), welfare (al-maslahah), and proportionality—as an interpretive tool to justify limited departures from faraidh in specific contexts without contravening Qur’anic injunctions. It concludes that reconstruction grounded in maqāṣid al-sharī‘ah provides a viable pathway to harmonize Islamic inheritance law with contemporary justice and Indonesia’s national legal framework